ANXIETY AND READINESS DIFFERENCES BETWEEN PRIMIGRAVIDA AND MULTIGRAVIDA MOTHERS TOWARDS CHILDBIRTH IN THE COVID-19 PANDEMIC - Mukronah Urvia; Woro Setia Ningtyas; Budi Utomo (UNIVERSITAS AIRLANGGA, 2023)
Background and Purpose : Corona Virus Disease 2019 (COVID-19) has now become a global pandemic, even in Indonesia. Pregnant women feel more and more anxious during the current COVID-19 pandemic, especially for 3rd trimester pregnant women who will give birth soon. Parity is one of the factors that can affect the level of anxiety of pregnant women in addition to the factors of the epidemic situation that can increase maternal anxiety. Childbirth readiness is one of the benchmarks for the success of the delivery process and this can indirectly contribute to the increase in MMR in Indonesia. Objective: Analyzing the differences in the level of anxiety and readiness towards childbirth in the COVID-19 pandemic between primigravida and multigravida mothers in their third trimester of pregnancy at the Duren Sawit District Health Center. Methods : This type of research is an observational study with a cross sectional design. Sampling was done by proportional random sampling method. The research instrument is a questionnaire. The method used in data analysis is the Mann-Whitney U test with the help of SPSS. Result : The sample of this study was 99 pregnant women in their third trimester of pregnancy. The level of anxiety in primigravida mothers is Severe level of anxiety (80.9%). Meanwhile, multigravida mothers have a Moderate level of anxiety (56.1%). The level of readiness of primigravida mothers is in the Inadequate category (57.1%). Meanwhile, multigravida mothers have a Good level of readiness (63.3%). The results of the Mann Whitney test showed that there was a significant difference between primigravida and multigravida mothers on the level of anxiety and readiness towards childbirth in the COVID-19 pandemic with a p value (0.000). Conclusion : There is a significant difference in the level of anxiety and readiness towards childbirth in the COVID-19 pandemic between primigravida and multigravida mothers in their third trimester of pregnancy at the Duren Sawit District Health Center.